Nutrition, cognition, and social emotion among preschoolers in poor, rural areas of South Central China: Status and correlates - Chen, Kevin Z.; Liu, Chengfang; Liu, Xinghua; Wang, Zimeiyi; Luo, Renfu; Li, Shaoping; Yu, Yanying; Alderman, Harold (MDPI, 2021)
Existing empirical evidence suggests that the prevalence of undernutrition in remote and poor, rural areas is still high among Chinese children. While evidence reveals that undernutrition may detrimentally affect child development, studies focusing on rural Chinese preschoolers are sparse. Using the baseline survey of a preschool’s free nutritious lunch pilot program, this study examined the relationship between child undernutrition and developmental outcomes among a preschool-aged sample in poor, rural areas of China. We conducted the baseline survey in Hunan province in south central China in September 2018. A total of 1293 preschoolers living in two (then) nationally designated poverty counties in rural Hunan served as our study sample. Children’s nutritional statuses were measured using height-for-age z-score, weight-for-age z-score, and anemia, while their cognitive and socio-emotional skills were assessed using the Wechsler Preschool and Primary Scale of Intelligence (WPPSI) and Strengths and Difficulties Questionnaire (SDQ), respectively. We find that 33% of sample preschoolers were anemic, whereas the incidences of stunting and wasting were 11% and 2%, respectively. About 54% of the sample children had delay in at least one of the developmental domains measured in this study. Our findings provide suggestive evidence supporting that children from certain backgrounds tend to experience worse nutritional and developmental outcomes than their counterparts. After controlling for socioeconomic status, we observed that both anemia and stunting were negatively associated with children’s cognitive performance; however, they were not associated with socio-emotional performance. As such, this study suggests that free lunch programs have the potential to change children’s developmental trajectory in preschool. We believe that our results will contribute to the debate surrounding whether the nutritious lunch program in China should be expanded to the preschool education level.